The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s41039-021-00147-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of computer-based virtual learning environments on nursing students’ mathematical learning in medication processes

Abstract: Computer-based virtual learning environments (CBVLEs) are potentially useful teaching tools for training nursing students in professional duties such as the mathematical tasks associated with medication processes. In this study, a CBVLE was designed with well-structured instructional activities such as interleaved practice and feedback. Mathematical medication scenarios and basic arithmetic exercises were integrated into the CBVLE. Four training conditions were used in the CBVLE to facilitate extra support for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
5
0
3
Order By: Relevance
“…Los entornos virtuales para el aprendizaje son espacios que permiten los procesos de aprendizaje formal a través de tareas y actividades, logrando así la meta de construcción de aprendizajes (Wang et al, 2018). Por su parte, Zwart et al (2021) señalan que los estudiantes obtienen experiencias de su proceso de aprendizaje mediante actividades virtuales. Picón (2020) indica que la modalidad virtual en el aprendizaje permite llevar a cabo actividades grupales y colaborativas de forma atractiva e interactiva, pero que además, como lo mencionan Baker y Chick (2006), la modalidad virtual no debe ser realizada al azar, sino que debe tener sus bases en la pedagogía, además de un contexto educativo.…”
Section: Modalidad Virtualunclassified
See 1 more Smart Citation
“…Los entornos virtuales para el aprendizaje son espacios que permiten los procesos de aprendizaje formal a través de tareas y actividades, logrando así la meta de construcción de aprendizajes (Wang et al, 2018). Por su parte, Zwart et al (2021) señalan que los estudiantes obtienen experiencias de su proceso de aprendizaje mediante actividades virtuales. Picón (2020) indica que la modalidad virtual en el aprendizaje permite llevar a cabo actividades grupales y colaborativas de forma atractiva e interactiva, pero que además, como lo mencionan Baker y Chick (2006), la modalidad virtual no debe ser realizada al azar, sino que debe tener sus bases en la pedagogía, además de un contexto educativo.…”
Section: Modalidad Virtualunclassified
“…A continuación se analizan las investigaciones identificadas con enfoque cuantitativo correspondientes al eje "Modalidad virtual para el aprendizaje" (Abdullah et al, 2021;Ambawati et al, 2021;Aramendiz y Córdova, 2019;Battaglia et al, 2019;Bautista et al, 2020;Bottini y Gillis, 2021;Huambachano et al, 2020;De Ponti et al, 2020; ie revista de investigación educativa de la Rediech vol. 13 • 2022 • e1598 • ISSN: 2448-8550 10 Durán, 2018; Fiangga et al, 2021;Ibáñez et al, 2018;Ihama y Eguasa, 2021;Inzunza et al, 2019;Kingsbury, 2020;Marciniak y Sallán, 2018;Matosas-López et al, 2019;Mercado et al, 2019;Mora-Vicarioli, 2019;Quesada-Castillo, 2019;Rincón et al, 2019;Luna y Hernández, 2020;Steehler et al, 2020;Zwart et al, 2021).…”
Section: Modalidad Virtual Para El Aprendizajeunclassified
“…The STEM approach has a positive effect on the development of scientific process skills and improves their attitudes and motivation. With the existence of a virtual lab based on the STEM approach, it is very impactful for students and has a very significant effectiveness and is an alternative for students in developing the learning process in schools and the real world (Zwart et al, 2021;Gunawan., 2017;Ying-Shao. 2017;Uğur., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies conducted in Iran, the quality of e-learning affects students' satisfaction with e-learning. For instance, a study conducted at Zahedan University of Medical Sciences by Zwart et al (2021) concluded that students perceived a significant difference between the current situation and the desired educational services in the service quality model, which consisted of five dimensions, including reliability, responsiveness, assurance, empathy, and tangibility. In the mentioned study, the majority of the students (81.6%) perceived a negative quality gap (18).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study conducted at Zahedan University of Medical Sciences by Zwart et al (2021) concluded that students perceived a significant difference between the current situation and the desired educational services in the service quality model, which consisted of five dimensions, including reliability, responsiveness, assurance, empathy, and tangibility. In the mentioned study, the majority of the students (81.6%) perceived a negative quality gap (18). According to other reports, learners' participation in an e-learning course could affect their attitude toward elearning given their different learning styles (19,20).…”
Section: Introductionmentioning
confidence: 99%